Cost analysis of prosthetic rehabilitation in young patients with Amelogenesis imperfecta. (December 2021) - Pousette Lundgren, Gunilla; Davidson, Thomas; Dahllöf, Göran
Abstract: Objectives: : Children and adolescents with amelogenesis imperfecta (AI) have extensive treatment needs, but costs have not been explored previously. We calculated the costs of prosthetic rehabilitation and analyzed whether costs of treatment begun in early adolescence are lower compared with in early adulthood. Methods: : Data from the dental records of 25 patients with AI and 25 age- and sex-matched controls were analyzed. Patients were followed for a mean period of 12.3 ± 1.5 years. Number of dental visits, dental treatment costs, and indirect costs were calculated during three time periods, before, during and after prosthetic therapy. Swedish national reference prices for general and specialist dental care were used. Results: : The mean number of visits was significantly higher in the AI group: 43.3 ± 19.7 (controls: 17.5 ± 19.8; p < .001). Mean total costs were 8.5 times higher for patients with AI: €16, 257 ± 5, 595 (controls: €1, 904 ± 993). Mean number of crowns made in patients with AI was 12 ± 7 (range 1 − 31). Indirect costs were significantly higher in the AI group and constituted 22% of the total costs. After crown therapy, costs between groups ceased to differ significantly. Calculations of total costs in the hypothetical scenario (discount rate at 3% annually) were €18, 475 for prosthetic rehabilitation began at age 12 years compared with €20, 227 if treatment began at 20 years of age. Conclusions: : Prosthetic rehabilitation costs for children and adolescents with AI can be high. Early crown therapy is associated with lower costs and a lower number of dental visits. Clinical Implications: Early crown therapy in children and adolescents with severe AI is a cost-reducing treatment associated with few complications and reduced need of dental care during adolescence compared with treatment begun at age 20.